The Use of Somatic Hypermutation for the Affinity Maturation of Therapeutic Antibodies - Bowers, Peter M. (Methods Mol Biol, 2018)
The engineering of antibodies and antibody fragments for affinity maturation, stability, and other biophysical characteristics is a common aspect of therapeutic development. Maturation of antibodies in B cells during the adaptive immune response is the result of a process called somatic hypermutation (SHM), in which the activation-induced cytidine deaminase (AID) acts to introduce mutations into immunoglobulin (Ig) genes. Iterative selection and clonal expansion of B cells containing affinity-enhancing mutations drive an increase in the overall affinity of antibodies. Here we describe the use of SHM coupled with mammalian cell surface display for the maturation of antibodies in vitro and the complementarity of these methods with the mining of immune lineages using next-generation sequencing (NGS).